2012
DOI: 10.2225/vol15-issue3-fulltext-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study for the kinetics of extracellular xylanases from Trichoderma harzianum and Chaetomium thermophilum

Abstract: Xylanases assume special importance in the paper and pulp industry as they replace toxic chemicals such as chlorine and chlorine dioxide for developing eco-friendly processes. This study evaluated xylanases produced by two fungi, the mesophilic fungus Trichoderma harzianum and a thermophilic fungus Chaetomium thermophilum. Among the polymeric substrates studied for xylanase production by both the fungi, birch wood xylan was found to be the best inducer of xylanases. Xylanases induction was subject to glucose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…Irfan and Syed (2012) determined pH 5.0 as optimal for xylanases produced by T. viride. The same was observed for T. harzianum xylanases (Ahmed et al, 2012).…”
Section: Biochemical Properties Of T Viride Xylanasesupporting
confidence: 78%
See 1 more Smart Citation
“…Irfan and Syed (2012) determined pH 5.0 as optimal for xylanases produced by T. viride. The same was observed for T. harzianum xylanases (Ahmed et al, 2012).…”
Section: Biochemical Properties Of T Viride Xylanasesupporting
confidence: 78%
“…(Irfan and Syed, 2012;Lopes et al, 2013). Conversely, the optimal temperature for T. harzianum xylanases was 60°C (Seyis and Aksoz, 2005;Ahmed et al, 2012).…”
Section: Biochemical Properties Of T Viride Xylanasementioning
confidence: 99%
“…Trichoderma species are well known for cellulase and xylanase production (Zhang et al 2017 has been reported by other authors with the activity value obtained using WH as substrate, it is observed that this can be an excellent substrate for the production of cellulolytic enzymes, contributing to the negative impact of this plant on water bodies. T. harzianum is widely utilized as a biological control agent (Saravanakumar et al 2016), and a thermostable xylanase, endo-β-1,4-xylanase and endo-β-1,3-glucanase have been previously purified and characterized from this fungus (Ahmed et al 2012). T. atroviride has been less studied; but some reports indicate that it possess a higher cellulase activity than T. reesei (Kovacs et al 2008) and it is present in urban stone surface (Paramo-Aguilera et al 2012).…”
Section: Saccharifying Enzyme Production By the Filamentous Fungi Gromentioning
confidence: 99%
“…We suggest that this phenomenon may be due to two reasons. First, the K M values reported for the T. harzianum cellulase are 2.4 gL −1 (de la Cruz et al 1995) and 3.8 gL −1 (Ahmed et al 2012), whereas the K M for its xylanases is 3.3 gL −1 (Chutani and Sharma 2015) and 4.8 gL −1 (El-Katatny et al 2001). The values reported by these authors suggest that xylanases have a greater affinity for their substrate than cellulases since they are capable of releasing a greater amount of monosaccharides.…”
Section: Saccharifying Enzyme Production By the Filamentous Fungi Gromentioning
confidence: 99%
“…2c, the maximum DCW increased as the pH decreased from 8.5 to 7.0, which means that high production of CMCase or xylanase was not consistent with increasement of cell growth at pH 7.0. We deduced that this may be related to the mycelial morphology as well as protein secretion of cells [35]. The protein concentration files (Fig.…”
Section: Effect Of Controlled Ph On Cellulase and Xylanase Productionmentioning
confidence: 90%